Bacteriological analysis of drinking water obtained from various public water coolers in Abha City, Saudi Arabia - Abdullah Abdulmohsen Alsabaani (Journal of Family Medicine and Primary Care)
Background: Water coolers are widely used in public spaces such as offices, schools, mosques, and fitness centers due to their provision of convenient access to potable water. However, inadequate management or maintenance of the water source can result in various health risks, including waterborne infections. Aim: This study highlights the critical need to assess and enhance the bacteriological quality of drinking water in public water coolers located in Abha, Saudi Arabia. Methods: This cross-sectional study collected 60 water samples from 48 public places in Abha, Saudi Arabia, using sterile containers and transported them under refrigeration to prevent bacterial overgrowth. The samples were analyzed for total coliforms and total plate count using the Most Probable Number (MPN) test and pour plate technique. Bacterial identification was conducted through subcultures, Gram staining, biochemical tests, and API 20E strips. Results: With a total of 60 water samples collected from diverse public places, the study found a concerning 20% positivity rate for total coliforms, indicating potential contamination. The presence of pathogenic bacteria such as Escherichia coli and Pseudomonas aeruginosa raises significant public health concerns, suggesting an elevated risk of waterborne infections. From a public health perspective, these findings underline the importance of regular inspection and maintenance of public drinking water coolers. Implementing stringent hygiene protocols, routine cleaning, and ensuring proper filtration could significantly reduce the risk of waterborne diseases. Conclusion: The study advocates for increased awareness and preventive measures to safeguard public health in Abha and similar regions. Maintaining high standards of water quality and hygiene in public areas is essential for preventing waterborne illnesses and ensuring that everyone has access to safe drinking water.